Perineural Invasion Is a Strong Prognostic Factor but Not a Predictive Factor of Response to Adjuvant Chemotherapy in Node-Negative Colon Cancer - Tu, Junhao; Yao, Zongxi; Wu, Wenqing; Ju, Jianxiang; Xu, Yinkai; Liu, Yulin (Frontiers in Oncology, 2021)
Purpose To validate the prognostic value and evaluate the predictive value of response to adjuvant chemotherapy of PNI in node-negative colon cancer. Methods Patients diagnosed with colon cancer between January 1, 2010 and December 31, 2015 were identified. Cancer-specific survival (CSS) was used as the survival endpoint and analyzed using the Kaplan–Meier method with log-rank test to evaluate the outcomes of different groups. Chi-square analysis was performed to evaluate different demographic and clinical features of patients between PNI-negative (PNI (-)) and PNI-positive (PNI (+)) groups. Univariate and multivariate Cox proportional hazard regression models were built to examine the relationship of demographic and clinical features and survival outcomes with the hazard ratios (HRs) and 95% confidence intervals (CIs). Results The receipt of chemotherapy was not an independent prognostic factor for CSS in T3 colon cancer without the presence of PNI (HR = 0.943, 95%CI = 0.802-1.108, P = 0.473, using no PNI and no chemotherapy as the reference); the receipt of chemotherapy was not an independent prognostic factor for CSS in T3 colon cancer with the presence of PNI (HR = 0.927, 95%CI = 0.613-1.400, P = 0.717, using the presence of PNI and no chemotherapy as the reference). The receipt of chemotherapy was independently associated with 34.0% decreased risk of cancer-specific mortality compared with those without the receipt of chemotherapy in T4 colon cancer without the presence of PNI (HR = 0.660, 95%CI = 0.559-0.779, P <0.001, using no PNI and no chemotherapy as the reference); the receipt of chemotherapy was independently associated with 36.0% decreased risk of cancer-specific mortality compared with those without the receipt of chemotherapy in T4 colon cancer with the presence of PNI (HR = 0.640, 95%CI = 0.438-0.935, P =0.021, using the presence of PNI and no chemotherapy as the reference). Conclusions The present study demonstrated the poor prognosis of PNI (+) in both stage I and II colon cancer. However, the presence of PNI was not a predictive factor of response to adjuvant chemotherapy in node-negative colon cancer.